2020
DOI: 10.1364/oe.398906
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid integrated InP-Si3N4 diode laser with a 40-Hz intrinsic linewidth

Abstract: We demonstrate a hybrid integrated and widely tunable diode laser with an intrinsic linewidth as narrow as 40 Hz, achieved with a single roundtrip through a low-loss feedback circuit that extends the cavity length to 0.5 meter on a chip. Employing solely dielectrics for single-roundtrip, single-mode resolved feedback filtering enables linewidth narrowing with increasing laser power, without limitations through nonlinear loss. We achieve single-frequency oscillation with up to 23 mW fiber coupled output power, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(102 citation statements)
references
References 49 publications
2
91
1
Order By: Relevance
“…Analysis of this spectrum reveals integrated and Lorentzian linewidths of 192 kHz and 8 kHz, respectively [19]. The fundamental line width of 8 kHz presented in this study is broader than that reported by others [5], [12], and is not fully understood, but may arise from mode competition within the cavity.…”
Section: Laser Testingcontrasting
confidence: 67%
“…Analysis of this spectrum reveals integrated and Lorentzian linewidths of 192 kHz and 8 kHz, respectively [19]. The fundamental line width of 8 kHz presented in this study is broader than that reported by others [5], [12], and is not fully understood, but may arise from mode competition within the cavity.…”
Section: Laser Testingcontrasting
confidence: 67%
“…Moreover, the relatively low refractive index contrast of Si3N4 waveguides makes the waveguide propagation loss lower and coupling between the III-V gain chip and the Si3N4 PIC easier, thereby guaranteeing good laser performances. A Si3N4 hybrid laser has been demonstrated with a 40-Hz linewidth and 20-mW output power [32]. A 100-mW high power Si3N4 hybrid laser with a 320-Hz intrinsic linewidth has also been reported [36].…”
Section: Introductionmentioning
confidence: 96%
“…For the hybrid lasers, various external cavity structures including Fabry-Perot (FP) cavities [24], distributed feedback (DFB) gratings [25], Bragg gratings [26,27], sampled grating distributed Bragg reflectors (SG-DBR) [28], interferometric structures [29], and Vernier microring resonators (MRRs) have been demonstrated on the silicon or Si3N4 platforms [21,[30][31][32]. Among them, the Vernier MRRs-based hybrid external cavity lasers (ECLs) have attracted lots of attention due to the merits of narrow passband response with a large free spectral range (FSR) and a small footprint.…”
Section: Introductionmentioning
confidence: 99%
“…The laser is built interfacing an InP gain section with a resonator in TriPleX: such structure demonstrated to provide an output power > 20 dBm, with a linewidth < 1 kHz [8]. The laser is first split into two paths.…”
Section: B Architecture Of the Spacebeam Beamformermentioning
confidence: 99%